Succesion between interments of Period V and architecture of Period VI at the Agua Caliente site, Cartago, Costa Rica - Vázquez, Ricardo (2022)
This work examines archaeological indications of two potential phases at the Agua Caliente site. The findings were yielded by rescue operations at a sector declared Architectural Historic Monument. The earlier context showed burials radiocarbon dated to A.D. 700-900, with bone preservation. The later evidence was represented by constructions adjacent to the larger structures of the site. Earth fills were deposited probably at the onset of Period VI (A.D. 1000-1550), sealing the area where burials of the second half of Period V (A.D. 300-1000) laid. The stratigraphic succession indicates, by A.D. 900/1000, the beginning of the apogee in civil work as a result of the exaltation in cacical prestige, and with it the appropriation of a prior funerary space.